EXPERENCIANDO NOVAS POSSIBILIDADES DE EDUCAÇÃO EM SAÚDE: A RÁDIO COMO FERRAMENTA DE INTERAÇÃO COM A COMUNIDADE - Guzzo, Patrícia C.; Cocco, Marta; Bastos, Ethel; Jahn, Alice d. C.; Resta, Darielli G.; Colomé, Isabel C. d. S.; Perdonsini, Leila G. B.; Nascimento, Kauana d.; Menezes, Luana P.; Correa, Camila F.; Pinno, Camila; Mendonça, Viviane (Salão do Conhecimento, 2013)
Resumo